Identifikasi Perilaku dan Karakteristik Awal Peserta Didik MI Manbaul Khairat - Juniar, Nur Haliza; Rizky, Rafa Fauziyyah; Amanda, Yunita (Lembaga Yasin AlSys, 2022)
Initial identification and characteristics of students is a process that teachers must go through in designing their learning. This is very important to determine the starting point of the learning material. In addition, this process also aims to avoid the occurrence of two things in the classroom, namely boredom and difficulty. Students who have mastered the material being taught will certainly feel bored, because they feel the material is repeated, while students who are taught have no basis at all on the material, of course, they will experience difficulties and even despair of the material being taught. In addition, this process also makes teachers understand the external factors that influence students in receiving lessons.